The United Nations Global Compact: Retrospect and Prospect. (March 2013) - Rasche, Andreas; Waddock, Sandra; McIntosh, Malcolm
This article reviews the interdisciplinary literature on the UN Global Compact. The review identifies three research perspectives, which scholars have used to study the UN Global Compact so far: a historical perspective discussing the Global Compact in the context of UN-business relations, an operational perspective discussing the composition and impact of its participants, as well as a governance perspective discussing the constraints and opportunities of the initiative as an institutionalized arena for addressing global governance gaps. The authors contrast these three perspectives and identify key empirical as well as conceptual scholarly contributions. The remainder of this article contains focused summaries of the articles selected for this Special Issue. All articles are introduced and evaluated against the background of the three research perspectives.